2023
DOI: 10.1002/adhm.202203307
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Fibroblast Activation Using an RGD‐Mutated Heparin Binding II Fragment of Fibronectin for Gingival Titanium Integration

Abstract: The formation of a biological seal around the neck of titanium (Ti) implants is critical for ensuring integration at the gingival site and for preventing bacterial colonization that may lead to periimplantitis. This process is guided by activated fibroblasts, named myofibroblasts, which secrete extracellular matrix (ECM) proteins and ECM‐degrading enzymes resolving the wound. However, in some cases, Ti is not able to attract and activate fibroblasts to a sufficient extent, which may compromise the success of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Consequently, functionalized PP surfaces provided stronger adhesion to human fibroblasts compared to untreated surfaces where adhesion relied on weaker and non-specific interactions such as van der Waals forces and electrostatic interactions. These results support our previous observations that HBII-RGD functionalization similarly promotes cellularity and spreading of human mesenchymal cells and foreskin fibroblasts cultured on titanium surfaces [ 43 , 44 ]. Furthermore, the effects of HBII-RGD on cellularity appeared to have a threshold below which these effects were nearly undetectable in our model.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consequently, functionalized PP surfaces provided stronger adhesion to human fibroblasts compared to untreated surfaces where adhesion relied on weaker and non-specific interactions such as van der Waals forces and electrostatic interactions. These results support our previous observations that HBII-RGD functionalization similarly promotes cellularity and spreading of human mesenchymal cells and foreskin fibroblasts cultured on titanium surfaces [ 43 , 44 ]. Furthermore, the effects of HBII-RGD on cellularity appeared to have a threshold below which these effects were nearly undetectable in our model.…”
Section: Discussionsupporting
confidence: 92%
“…The HBII-RGD fragment was produced by standard recombinant DNA methods as previously described [ 43 , 44 ]. Briefly, the DNA fragment of HBII was inserted into the pGEX-6-P1 plasmid (GE Healthcare, Buckinghamshire, UK) and transformed into DH5α cells (Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the modification of titanium implants with bioactive substance can greatly facilitate the adhesion of cells to the surface of titanium implants. [31][32][33][34][35][36] Figure 5 demonstrates that on day 1 and 3 of incubation, the TiOH surface exhibited the highest cell adhesion and viability, while after 5 days of incubation, no significant difference in cell number was observed among the groups. This indicates that both surface roughness and wettability influence cell proliferation on material surfaces, and the microenvironment in which the cells grow also plays a crucial role in regulating cell proliferation and differentiation.…”
Section: Analysis Of Osteogenic Capacitymentioning
confidence: 99%